Metal Cations in G-Quadruplex Folding and Stability - Bhattacharyya, Debmalya; Mirihana Arachchilage, Gayan; Basu, Soumitra (Frontiers in Chemistry, 2016)
This review is focused on the structural and physico-chemical aspects of metal cation coordination to G-Quadruplexes (GQ) and their effects on GQ stability and conformation. G-Quadruplex structures are non-canonical secondary structures formed by both DNA and RNA. G-quadruplexes regulate a wide range of important biochemical processes. Besides the sequence requirements, the coordination of monovalent cations in the GQ is essential for its formation and determines the stability and polymorphism of GQ structures. The nature, location and dynamics of the cation coordination and their impact on the overall GQ stability are dependent on several factors such as the ionic radii, hydration energy and the bonding strength to the O6 of guanines. The intracellular monovalent cation concentration and the localized ion concentrations determine the formation of GQs and can potentially dictate their regulatory roles. A wide range of biochemical and biophysical studies on an array of GQ enabling sequences have generated at a minimum the knowledge base that allows us to often predict the stability of GQs in presence of the physiologically relevant metal ions, however, prediction of conformation of such GQs is still out of the realm.